2014
DOI: 10.1182/blood-2014-02-550327
|View full text |Cite
|
Sign up to set email alerts
|

In utero depletion of fetal hematopoietic stem cells improves engraftment after neonatal transplantation in mice

Abstract: • In utero injection of an antibody against the c-Kit receptor can effectively deplete host HSCs in mice.• In utero depletion of host HSCs leads to significantly increased engraftment after neonatal congenic hematopoietic cell transplantation.Although in utero hematopoietic cell transplantation is a promising strategy to treat congenital hematopoietic disorders, levels of engraftment have not been therapeutic for diseases in which donor cells have no survival advantage. We used an antibody against the murine c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
42
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(43 citation statements)
references
References 52 publications
0
42
0
Order By: Relevance
“…CD34 1 cells were isolated and transplanted into fetal mice at embryonic day 13.5 (E13.5) or E14.5 as previously described 23 with or without preconditioning with ACK2. 17 Chimerism levels were checked at 4-week intervals and at harvest using flow cytometry and immunohistochemistry.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…CD34 1 cells were isolated and transplanted into fetal mice at embryonic day 13.5 (E13.5) or E14.5 as previously described 23 with or without preconditioning with ACK2. 17 Chimerism levels were checked at 4-week intervals and at harvest using flow cytometry and immunohistochemistry.…”
Section: Methodsmentioning
confidence: 99%
“…11,12 Clinically, IUHCT has been successful for fetuses with severe combined immunodeficiency (SCID), 13,14 but therapeutic uses for other diseases, including hemoglobinopathies, have seen limited success. 15 Further investigations identified multiple barriers to successful engraftment, including lack of space within the hematopoietic niche 16,17 and the maternal immune system. 2,18 Among available animal models of IUHCT, the fetal mouse remains an efficient and reproducible model to study the differentiation of stem cells in a nonirradiated host.…”
Section: Introductionmentioning
confidence: 99%
“…Future development of isoformspecific inhibitors of HMGB1 may mitigate excessive inflammation and thrombosis without affecting the beneficial effects of HMGB1 in the resolution of inflammation and tissue repair. 10 Conflict-of-interest disclosure: The author declares no competing financial interests. n REFERENCES Musical chairs: in utero HCT via mobilization…”
mentioning
confidence: 99%
“…9 It has also been shown that ACK2 can be safely injected directly into fetal mice; when followed by a transplant of congenic HSCs, it results in approximately 15% multilineage donor engraftment. 10 Such a combined approach would consist of the music starting (mobilization of host HSCs from the endogenous niche via blockade of a4b1-integrin), followed by removal of some of the participants from the game (partial depletion of host HSCs via antic-kit), and then followed by addition of the new contestants (infusion of the donor HSCs). Once the music stops (fading of the a4b1-integrin blockade), the overabundance of donor HSCs would hopefully have a competitive advantage for successfully sitting down into the chairs (the HSC niche).…”
mentioning
confidence: 99%
“…However, the benefit for the individual patient has to be balanced against the risks of adverse effects [7]. Antibody-based conditioning alone [16,17] appears to be less effective than as part of a minimal intensity regimen [18].…”
mentioning
confidence: 99%